External and internal maximal intensity periods of elite youth male soccer matches - Kim, S.; Emmonds, S.; Bower, P.; Weaving, D. (Journal of Sports Sciences, 2023)
Understanding the maximal intensity periods (MIP) of soccer matches can optimise training prescription. The aim was to establish differences between positions and other contextual factors (match location, match outcome, playing formation and score line) for both external and internal MIP variables and to investigate the differences in the match start time between MIP variables. Maximal moving averages (1 to 10 min) for average speed, high-speed running (5.5-7 m·s-1), sprinting (>7 m·s-1; all m·min-1), average acceleration/deceleration (m·s-2) and heart rate (bpm, % maximal) were calculated from 24 professional youth players across 31 matches. Linear mixed models determined differences in MIP variables between positions, contextual factors and in the match start time of MIPs. Trivial to large positional differences existed in maximal external intensities while central defenders presented the lowest heart rate. It was unclear whether maximal intensities were influenced by contextual factors. MIPs for average speed, acceleration/deceleration and heart rate tend to occur concurrently (ES = trivial) within the first 30 min, while high-speed running and sprinting are likely to occur concurrently (ES = trivial) throughout a whole match. Practitioners could target maximising average speed and average acceleration/deceleration in technical-tactical based training to maximise heart rate responses.